Chapter 35 - Gene therapy, neurotrophic factors and spinal cord regeneration - Blesch, Armin; Fischer, Itzhak; Tuszynski, Mark H. (Spinal cord injury, 2012)
Significant advances have been made in understanding the mechanisms that limit axon regeneration in the adult mammalian central nervous system and in addressing some of the obstacles for axon growth. Despite this progress numerous challenges remain to achieve regeneration of a large number of axons sufficient to mediate functional improvement. Given the complexity of injury-induced changes in axon, cell body, and parenchyma surrounding a spinal cord lesion, it seems likely that multiple factors both intrinsic and extrinsic to injured neurons have to be addressed to augment axon regeneration and useful reorganization of spared circuitry. Neurotrophic factors have been shown to be one potent means to increase the number and range of regenerating axons, to guide regenerating axons across a lesion site, and to augment regenerative cell body responses to injury. In this chapter we will review the potential and current limitations of neurotrophic factors and gene therapy, in combination with cellular transplants, for axon regeneration and sprouting in the injured spinal cord.